A Study of Cognitive Technology OFDM System and Frame Structure - Hua Hou; Wei Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
For mobile communication system with multi-service of multiple users, spectrum utilization rate is low and user's QoS requirements need to be improved. The paper proposed a cross-layer based on cognitive radio technology and OFDM technology model and designed the core technology of this frame structure model  such as service division, spectrum sensing and spectrum aggregation in detail. Comprehensive judgment through the service needs of different users, and the spectrum holes judgment, not only meet different user’s QoS, but also improve spectrum utilization and increase the system suitability. Finally, the simulation analysis of the model’s performance shows that the model can not only reasonable use of the spectrum holes, and better meet the user’s QoS requirements.